Marriage and childbearing in patients with epilepsy in Turkey - Tokuç, Firdevs Ezgi Uçan; Genç, Fatma; Göksu, Eylem Özaydın; Erdal, Abidin; Gömceli, Yasemin Biçer (Frontiers in Neurology, 2024)
Introduction For epilepsy, a common neurological disorder, brings psychosocial challenges like stigma, employment difficulties, and barriers to marriage and childbearing. Stigma often stems from misconceptions and societal beliefs, particularly in less developed regions like Turkey. However, research on the marital and childbearing experiences of epilepsy patients in such settings is limited. We aimed to research the marriage and childbearing behaviors of men and women with epilepsy. Methods We conducted a cross-sectional study involving 215 adult epilepsy patients at Antalya Training and Research Hospital between 2019 and 2022. Patients were asked questions about marriage and having children on prepared questionnaires. Result The gender distribution of the 215 patients included in the study was revealed to be 62.3% (134) females and 37.7% (81) males. 71.6% of patients were married, and 12.7% had no children. 33.3% of these patients stated that they did not desire children because of the disease. A statistically significant correlation was observed between the duration of the disease and being unmarried. A significant correlation was observed between age at disease onset and number of children. Conclusion Our study revealed the effects of individuals with epilepsy on marriage and childbearing, and as we know, it is the first study conducted in Turkey on childbearing attitudes in individuals with epilepsy. Despite medical and social developments, epilepsy is still one of the most stigmatized diseases, and the disease has considerable negative effects on marriage and fertility. Our study supported the findings of a small number of previous similar studies on this subject and additionally showed that the likelihood of having children decreased in patients using multiple ASM, and on the other hand, it showed that marriage positively affected patients in terms of social support.